P31 Optimisation of smart-pump drug library functionality – supporting national standardisation. Issue 5 (20th April 2022) - Sutton, Sharon; McGrath, Eimear; Breatnach, Cormac; Howlett, Moninne
Abstract : Aim: To optimise smart-pump functionality as part of an ongoing multi-phase project to develop a national smart-pump drug library of standard concentration infusions (SCIs) suitable for paediatric and neonatal patients in paediatric, maternity and adult hospitals. Method: Multidisciplinary working groups with representation from paediatric, neonatal and adult intensive care units (ICUs) were established. Agreed lists of SCIs for separate neonatal and paediatric drug libraries were developed. A paediatric SCI drug library, originally developed by the lead site in 2012 containing 42 drug lines (primarily continuous infusions) within a single care-unit, was used as the primary reference source. A Microsoft Excel® SCI flow rate calculator was developed which allowed comparison of traditional infusion practices against hypothetical SCIs. Acquisition of drug library content management system (CMS) by the lead site facilitated exploration and optimisation of CMS functionality and library architecture supporting comprehensive drug library development. A range of care units, clinically judicious limits, weight bands and therapeutic categories were designed to accommodate diverse paediatric and neonatal populations. Agreed parameters were manually input to the CMS before exporting as files for pump upload. For each iteration, drug library files are uploaded onto infusion pumps for testing and verification against CMS-exported reports, ensuring rigorous validation processes. Reference material and rationale for decisions made were collated and stored using a commercial medicines information software application. Results: A master library containing 216 drug lines within 7 speciality-specific care-units and 7 therapeutic categories across 5 weight bands was developed. Drug lines included: majority of commonly used medications (both continuous and intermittent, including loading and bolus doses), parenteral nutrition, IV fluids and blood products. This represented a 270% increase on the originator paediatric library. Individual drug libraries were developed for use in: tertiary paediatric sites (with PICUs), maternity hospitals (with NICUs/Special-care baby units), adult ICUs/regional hospitals. Supporting documentation, including training materials, standard operating procedures, and SCI tables were developed. Updates to the relevant monographs of the lead site's paediatric formulary, available as an app and on hospital desktops, were made to reflect drug library contents. Implementation has occurred in all paediatric intensive care units (PICUs) and tertiary paediatric emergency departments (EDs), paediatric and neonatal transport services and 6 of 19 neonatal sites. Implementation into the pilot adult ICU is due in Q3 2021, with phased implementation into remaining neonatal sites, adult ICUs and EDs of regional hospitals planned. Conclusion: Optimisation of smart-pump CMS functionality can support development of comprehensive drug libraries suitable for use in a range of clinical settings. Centralised processes, with dedicated pharmacy resources, are key to standardisation of infusion processes at a national level in line with internationally recognised best practices. 1–3 Reference: Institute for Safe Medication Practices, ISMP. Guidelines for Optimizing Safe Implementation and Use of Smart Infusion Pumps 2020 Available at: https://www.ismp.org/guidelines/safe-implementation-and-use-smart-pumps] Royal College of Paediatrics and Child Health (RCPCH)/Neonatal Paediatric Pharmacists Group (NPPG). Standardising intravenous infusion concentrations in children in the UK 2021 Available at: https://www.rcpch.ac.uk/resources/standardising-intravenous-infusion-concentrations-children-uk] American Society of Health-System Pharmacists, ASHP. Standardize 4 Safety 2018 Available at: https://www.ashp.org/pharmacy-practice/standardize-4-safety-initiative